1981
DOI: 10.1080/03637758109376058
|View full text |Cite
|
Sign up to set email alerts
|

Studies in interpersonal epistemology: III. Anticipated interaction, self‐monitoring, and observational context selection

Abstract: a Professor of communication studies , Northwestern University , b Graduate student in communication studies ,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
66
0

Year Published

1984
1984
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(70 citation statements)
references
References 9 publications
2
66
0
Order By: Relevance
“…Berger and Douglas (1981), for example, discovered differences in the perception of how informative formal and informal situations were in reducing uncertainty by level of self-monitoring: Low self-monitors perceived formal situations as more informative, while high self-monitors saw informal situations as more informative. This finding is consistent with Ickes and Barnes (1977) who reported high self-monitors initiated and regulated conversations more, initiated more conversational sequences, and had a greater need to talk than low self-monitors.…”
Section: Selj-mon Itoringmentioning
confidence: 95%
See 1 more Smart Citation
“…Berger and Douglas (1981), for example, discovered differences in the perception of how informative formal and informal situations were in reducing uncertainty by level of self-monitoring: Low self-monitors perceived formal situations as more informative, while high self-monitors saw informal situations as more informative. This finding is consistent with Ickes and Barnes (1977) who reported high self-monitors initiated and regulated conversations more, initiated more conversational sequences, and had a greater need to talk than low self-monitors.…”
Section: Selj-mon Itoringmentioning
confidence: 95%
“…Recent work by Berger and his associates (Berger, 1979;Berger & Perkins, 1977;Berger & Douglas, 1981) suggests communication in initial interactions is influenced by self-monitoring. Berger and Douglas (1981), for example, discovered differences in the perception of how informative formal and informal situations were in reducing uncertainty by level of self-monitoring: Low self-monitors perceived formal situations as more informative, while high self-monitors saw informal situations as more informative.…”
Section: Selj-mon Itoringmentioning
confidence: 95%
“…Uncertainty reduction theory, which we used as the theoretical basis of this study, has been highly successful, of course, in confirming predictions about initial interactions and zero-history encounters (Berger & Douglas, 1981;Berger & Perkins, 1978;Hewes et al, 1985;Kellerman & Berger, 1984). The theory, of course, focuses primarily on early information processing and related cognitions and behaviors.…”
Section: Summary Of Studymentioning
confidence: 94%
“…Research generally provides support for the information-seeking strategies of uncertainty reduction theory (Sunnafrank, 1986). Indeed, research has shown that passive and active strategies help individuals gain information about a target (e.g., Berger & Douglas, 1981;Berger & Perkins, 1978;Hewes, Graham, Doelger, & Pavitt, 1985). For example, Hewes et al (1985) conducted research in the area of active strategies of information seeking.…”
mentioning
confidence: 97%
“…Seminal works by Heider (1958) and Kelley (1973), among others (e.g., Jones & Davis, 1965), assert that people are motivated to predict and understand other peoples' behavior. Specifically, when uncertainty is aroused, people are motivated to increase their approach oriented behavior (e.g., behavioral attraction) to determine the viability of a potential relationship, usually via efforts to monitor the other person's behavior (Berger & Douglas, 1981;Berger & Perkins, 1978), seeking out and asking the target person more questions, among other strategies (Berger, 1979;Berger & Bradac, 1982). For example, in a series of field studies investigating attraction of preoperative and postoperative hospital patients, Kulik and colleagues (Kulik & Mahler, 1989;Kulik, Mahler, & Moore, 1996;Kulik, Moore, & Mahler, 1993) found that patients facing surgery opted to spend time (as a measure of behavioral attraction) with those who were capable of meeting their desire for information (i.e., post-operative patients), compared to those who were less capable (i.e.…”
mentioning
confidence: 99%